Aptamers: An Emerging Tool for Diagnosis and Therapeutics in Tuberculosis - Srivastava, Shruti; Abraham, Philip Raj; Mukhopadhyay, Sangita (Frontiers in Cellular and Infection Microbiology, 2021)
Tuberculosis (TB) has been plaguing human civilization since centuries and currently around one-third of the global population is affected with TB. Development of novel interventions tools for early diagnosis and therapeutics against Mycobacterium tuberculosis (M.tb) are main thrust area in today’s scenario. In this direction global efforts were made to use aptamers, the chemical antibodies as tool for TB diagnostics and therapeutics. This review describes the various aptamers introduced for targeting M.tb and highlights the need for development of novel aptamers to selectively target virulent proteins of M.tb for vaccine and anti-TB drugs. The objective of this review is to highlight the diagnostic and therapeutic application of aptamers used for tuberculosis. The discovery of aptamers, SELEX technology, different types of SELEX development processes, DNA and RNA aptamers reported for diseases and pathogenic agents as well have also been described in detail. But the emphasis of this review is on the development of aptamers which can block the function of virulent mycobacterial components for developing newer TB vaccine candidates and/or drug targets. Aptamers designed to target M.tb cell wall proteins, virulent factors, secretory proteins or combination could orchestrate advanced diagnosis and therapeutic measures for tuberculosis.